PLASTIK NANOKOMPOSIT KITOSAN-LEMPUNG-TiO2 - , Endaruji Sedyadi, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Plastic nanocomposite of chitosan-clay-TiO2 with increased mechanical, UV-Visible absorption and reflection properties has been prepared. Plastic preparation variables consisting of temperature (45, 65 and 85 Â°C), clay content (0, 1, 3, 5 and 15% (w/w)) and crystalline type of TiO2 as UV absorber material (anatase and rutile) were studied. Chitosan obtained from chitin deacetylation of shrimp waste was used as a starting material for plastic preparation using solvent casting method. Results showed that optimum drying temperature for preparation of chitosan plastic was at 65 Â°C for 7 hours with a good tensile strength of 18.68 MPa. It is also shown that chitosan-clay nanocomposite plastics having higher tensile strength than those of chitosan. Addition of 5% (w/w) clay produced a plastic with an increased tensile strength of 28.16% higher (23.94 MPa). TEM images showed that clay structure was dispersed in chitosan polymer as an exfoliated structure. Chitosan-clay-TiO2 rutile plastic has wider UV absorption in UV-C (100-290 nm) and UV-B (290-320 nm) range and higher visible reflection than chitosan-clay-TiO2 anatase plastic. The opacity of chitosan plastic was 6.75 x 10-4 nm OD/micron. Addition of TiO2 anatase and rutile increased plastic opacity to 18 x 10-4 nm OD/micron (106.7%) and 13.75 x 10-4 nm OD/micron (103.7%), respectively. Plastic nanocomposites of chitosan-clay-TiO2 rutile resulted in better mechanical and light absorption properties than commercial plastic.